2012
DOI: 10.1111/j.1467-9604.2011.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with autistic spectrum disorder: parental experiences of raising a child with autistic spectrum disorder (ASD)

Abstract: The focus of the study was to explore parental experiences of raising a child with autistic spectrum disorder (ASD). A mixed‐method approach consisting of questionnaires and semi‐structured interviews was used in order to elicit parental perspectives of raising a child with ASD. Two semi‐structured interviews were conducted with parents of children with ASD. Questionnaires were sent to parents of children with ASD in two special schools. The findings indicate that although each of the parents had a child with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
3
20
1
2
Order By: Relevance
“…When compared with parents of typically developing children, parents of children with ASD reported more frequent use of distancing and escaping, but less use of social support (Sivberg 2002). The lower use of social support is somewhat unusual as compared to other studies reviewed in this section and past studies, whereby social support was reported to be one of the most frequently employed coping strategy (e.g., Boyd 2002;Glazzard and Overall 2012;Hall 2012;Lin et al 2008;Luther et al 2005;Twoy et al 2007).…”
Section: Quantitative Studies Using Brief Cope Cope F-copes Chip mentioning
confidence: 61%
See 2 more Smart Citations
“…When compared with parents of typically developing children, parents of children with ASD reported more frequent use of distancing and escaping, but less use of social support (Sivberg 2002). The lower use of social support is somewhat unusual as compared to other studies reviewed in this section and past studies, whereby social support was reported to be one of the most frequently employed coping strategy (e.g., Boyd 2002;Glazzard and Overall 2012;Hall 2012;Lin et al 2008;Luther et al 2005;Twoy et al 2007).…”
Section: Quantitative Studies Using Brief Cope Cope F-copes Chip mentioning
confidence: 61%
“…Secondly, data collection tools are critical to the conceptualization of the coping construct. For instance, in open-ended interviews, unexplored coping strategies that parents have developed over experience could be tapped via parents' open sharing about their experiences (Glazzard and Overall 2012). On the other hand, parent responses on a theory-based coping questionnaire are limited by the theoretical construct defining the questionnaire (Skinner and Zimmer-Gembeck 2007).…”
Section: Methodological Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…These topics are considered key in parent training (Patterson, Smith, and Mirenda 2011;Schultz, Schmidt, and Stichter 2011); and interventions focusing on communication, playing with peers and positive, proactive approaches to problem behaviour are identified by the national Research Council (2001) as educational priorities for children with autism. Furthermore, numerous studies identify that problem behaviours are a major stressor for parents of children with (Glazzard and overall 2012;Hall and Graff 2011;nealy et al 2012;Weiss and Lunsky 2011) so it unsurprising this is prioritised. It seems reasonable to conclude that parents in these three countries -as elsewhere -feel the need for support with these key issues.…”
Section: Discussionmentioning
confidence: 99%
“…R aising children with autism spectrum disorder (ASD) can be challenging (Montes & Halterman, 2006). Examples of challenges include increased time required for nurturing the child (Smith et al, 2010); need to reorganize daily occupations around the child's special behaviors (Glazzard & Overall, 2012); lack of information regarding caring for and managing the child; and absence of support because of lack of acceptance among extended family members, social rejection, and lack of public awareness (Dababnah & Parish, 2013). Securing and managing educational and other services can be difficult; parents might have to take their child to therapy or school and carry out home exercise programs prescribed by therapists (Hodgetts, McConnell, Zwaigenbaum, & Nicholas, 2014).…”
mentioning
confidence: 99%